MO069: Therapeutic Effects of Semaglutide as Mono and Combination Treatment with Lisinopril in a Mouse Model of Hypertension-Accelerated Diabetic Kidney Disease. (3rd May 2022) - Christensen, Michael; Dalbøge, Louise S; Secher, Thomas; Gravesen Salinas, Casper; Ida, Rune; Björk Hansen, Henrik; Fink, Lisbeth N; Viberg Østergaard, Mette
Abstract: BACKGROUND AND AIMS: Obesity, hyperglycemia and hypertension are critical risk factors for the onset and progression of diabetic kidney disease (DKD). Emerging evidence suggests that sodium-glucose cotransporter-2 (SGLT2) inhibitors and glucagon-like peptide-1 receptor (GLP-1R) agonists improve cardiovascular and renal outcomes in type 2 diabetes patients. We have recently profiled the effects of SGLT2 and angiotensin-converting enzyme (ACE) inhibition in a model of advanced DKD facilitated by adeno-associated virus (AAV)-mediated renin overexpression in uninephrectomized (UNx) diabetic db/db mice (Østergaard et al ., AJP Renal Physiol 321: F149–F161, 2021). In the present study, we evaluated the nephroprotective effects of the long-acting GLP1R agonist semaglutide, a long-acting GLP1R agonist currently approved for diabetes and obesity treatment and in clinical development for DKD. Semaglutide was profiled with and without combination treatment with lisinopril, a standard ACE inhibitor, in the db/db UNx-ReninAAV mouse model of DKD. METHOD: Female db/db mice received a single intravenous injection of reninAAV 1 week prior to UNx. Six weeks post-nephrectomy, mice were randomized into treatment groups based on body weight and blood glucose in the fed state, and received vehicle (SC, QD), semaglutide 30 nmol/kg or semaglutide 30 nmol/kg (SC, QD) in combination with lisinopril 30 mg/kg (PO, QD) for 11 weeks. Treatment endpoints included blood pressure, plasma/urine biochemistry and histomorphometric markers of kidney injury. RESULTS: Vehicle-dosed db/db UNx-ReninAAV mice developed hallmarks of hypertensive DKD characterized by severe albuminuria and advanced glomerulosclerosis. Compared with vehicle, semaglutide significantly reduced fed blood glucose and hemoglobin A1C levels, whereas no significant effect on plasma insulin was observed. Semaglutide significantly reduced both diastolic and systolic blood pressure as well as albuminuria and urine kidney injury molecule-1 (KIM-1) levels. Semaglutide improved kidney histopathology with notable reductions in glomerulosclerosis severity and percent area of KIM-1 staining. Combined lisinopril treatment led to further improvements in blood pressure, albuminuria and glomerulosclerosis. Semaglutide with and without lisinopril coadministration did not influence plasma urea, cystatin C and kidney CD11 expression. CONCLUSION: Semaglutide improved disease hallmarks in the db/db UNx-ReninAAV mouse model of advanced DKD. Further benefits on renal functional and histological markers were obtained by combination with antihypertensive standard-of-care treatment.